Physical activity of young people – meaning of family traditions - Grabowska, Barbara; Jakubowska, Luba (EDUsfera. Ewa Jurczyk-Romanowska, 2019)
The aim of the work was to investigate the significance of the basic upbringing environment – the family – to the undertaking of physical activity by young people. The research was conducted among your people (N=629) aged 19 to 23. Among the research participants 474 (75.4%) came from big cities, and 155 (24.6%) from smaller localities. All of the participants were university students. A questionnaire on physical activity was used in the research (Grabowska, 2017).
Keywords: family; physical education; physical activity; young people; free time